Getting a grip on tetrapod grasping: form, function, and evolution. (3rd January 2013) - Sustaita, Diego; Pouydebat, Emmanuelle; Manzano, Adriana; Abdala, Virginia; Hertel, Fritz; Herrel, Anthony
ABSTRACT Human beings have been credited with unparalleled capabilities for digital prehension grasping. However, grasping behaviour is widespread among tetrapods. The propensity to grasp, and the anatomical characteristics that underlie it, appear in all of the major groups of tetrapods with the possible exception of terrestrial turtles. Although some features are synapomorphic to the tetrapod clade, such as well‐defined digits and digital musculature, other features, such as opposable digits and tendon configurations, appear to have evolved independently in many lineages. Here we examine the incidence, functional morphology, and evolution of grasping across four major tetrapod clades. Our review suggests that the ability to grasp with the manus and pes is considerably more widespread, and ecologically and evolutionarily important, than previously thought. The morphological bases and ecological factors that govern grasping abilities may differ among tetrapods, yet the selective forces shaping them are likely similar. We suggest that further investigation into grasping form and function within and among these clades may expose a greater role for grasping ability in the evolutionary success of many tetrapod lineages.